2019
DOI: 10.1186/s13021-019-0125-9
|View full text |Cite
|
Sign up to set email alerts
|

Impact of modelling choices on setting the reference levels for the EU forest carbon sinks: how do different assumptions affect the country-specific forest reference levels?

Abstract: Background: In 2018, the European Union (EU) adopted Regulation 2018/841, which sets the accounting rules for the land use, land use change and forestry (LULUCF) sector for the period 2021-2030. This regulation is part of the EU's commitments to comply with the Paris Agreement. According to the new regulation, emissions and removals for managed forest land are to be accounted against a projected forest reference level (FRL) that is estimated by each EU Member State based on the continuation of forest managemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 21 publications
0
27
0
Order By: Relevance
“…Nabuurs et al [ 4 ], upon an analysis of harvesting possibilities based on the EFISCEN model, suggested that the 26 countries together can increase harvests complying the continuation of management practices criteria without creating debits. Forsell et al [ 5 ] examined the role of different computational assumptions, finding technicalities such as the starting year for the projection, stratification criteria for the area of managed forest land, and simulated timing of individual management activities to have less impact compared to assumptions on climate change or allocation of management practices. For their analyses, Forsell et al [ 5 ] coupled forest dynamics and GHG modelling based on the G4M and WoodCarbonMonitor frameworks.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Nabuurs et al [ 4 ], upon an analysis of harvesting possibilities based on the EFISCEN model, suggested that the 26 countries together can increase harvests complying the continuation of management practices criteria without creating debits. Forsell et al [ 5 ] examined the role of different computational assumptions, finding technicalities such as the starting year for the projection, stratification criteria for the area of managed forest land, and simulated timing of individual management activities to have less impact compared to assumptions on climate change or allocation of management practices. For their analyses, Forsell et al [ 5 ] coupled forest dynamics and GHG modelling based on the G4M and WoodCarbonMonitor frameworks.…”
Section: Introductionmentioning
confidence: 99%
“…Forsell et al [ 5 ] examined the role of different computational assumptions, finding technicalities such as the starting year for the projection, stratification criteria for the area of managed forest land, and simulated timing of individual management activities to have less impact compared to assumptions on climate change or allocation of management practices. For their analyses, Forsell et al [ 5 ] coupled forest dynamics and GHG modelling based on the G4M and WoodCarbonMonitor frameworks.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Foreign scholars have paid more attention to carbon pools of forest [10][11][12] than carbon sources/sinks in agricultural or farmland system. But the latter is arousing a growing interest in the academic circle.…”
Section: Introductionmentioning
confidence: 99%